2013
DOI: 10.4037/ajcc2013784
|View full text |Cite
|
Sign up to set email alerts
|

Role Responsibilities in Mechanical Ventilation and Weaning in Pediatric Intensive Care Units: A National Survey

Abstract: Background Organizational processes affect the duration of mechanical ventilation in adult and pediatric intensive care units, but surprisingly little is known about role responsibilities for mechanical ventilation and weaning and related contextual factors that may influence timely liberation from mechanical ventilation. Objective To determine the professional group and seniority of clinicians responsible for key decisions regarding ventilation and weaning; use of ventilation protocols and automated closed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
2
13
0
3
Order By: Relevance
“…This is also confirmed in two recent studies about interdisciplinary collaborative decision‐making regarding ventilation and weaning (Rose et al , ; Blackwood et al , ). Enhanced communication and collaboration between professionals could probably avoid unnecessary prolonged ventilation and weaning (Rose et al , ; Blackwood et al , ). We speculate that manipulating these specific organizational characteristics (interdisciplinary collaboration, effective communication, leadership support and organizational aspects like nurse‐to‐patient ratio and ongoing education) may be an effective strategy to improve adherence to protocols, which deserves to be explored and evaluated in further implementation projects (Sinuff et al , ).…”
Section: Discussionsupporting
confidence: 67%
“…This is also confirmed in two recent studies about interdisciplinary collaborative decision‐making regarding ventilation and weaning (Rose et al , ; Blackwood et al , ). Enhanced communication and collaboration between professionals could probably avoid unnecessary prolonged ventilation and weaning (Rose et al , ; Blackwood et al , ). We speculate that manipulating these specific organizational characteristics (interdisciplinary collaboration, effective communication, leadership support and organizational aspects like nurse‐to‐patient ratio and ongoing education) may be an effective strategy to improve adherence to protocols, which deserves to be explored and evaluated in further implementation projects (Sinuff et al , ).…”
Section: Discussionsupporting
confidence: 67%
“…Nurses who have not worked in critical care are likely to enter the ICU environment with limited knowledge on MV; therefore, comprehensive CE on MV provided by ICUs to educate nurses is essential (Blackwood et al, ; Rose et al, ). MV is taught comprehensively at the post‐graduate level as part of critical care courses; however, post‐graduate education in critical care is not mandatory prior to working in the ICU (Rose et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Management of MV is complex and dynamic, requiring extensive knowledge and skills to perform complex, accurate and timely decision‐making to provide safe, best‐practice care and reduce the risk of complications (Blackwood et al, ; Duff, ; Fenstermacher and Hong, ; Rose and Gerdtz, ). Continuing education (CE) plays a critical role in building and maintaining knowledge by developing clinical reasoning and evaluation skills, promoting self‐reflection and supporting safe practice and quality care (Al‐Majid et al, ; Cooper, ; Farnell and Dawson, ; Levett‐Jones, ; Lindner, ) given that undergraduate nursing students have limited exposure to MV.…”
Section: Introductionmentioning
confidence: 99%
“…54 A recent survey of PICU staff in the United Kingdom suggested that automated or closed-loop systems were available in 18% of their ICUs. 55 Systematic reviews by Rose and Colleagues in 2012 and 2013 56 compared studies of automated and nonautomated tools for weaning. They noted that the number of studies was limited and there was substantial heterogeneity in trial designs, but that the findings suggested that such systems may reduce weaning time, duration of ventilation, and duration of ICU stay, particularly in mixed or medical ICU populations.…”
Section: Beyond If…then Rulesmentioning
confidence: 99%